Comparing greenhouse gas emissions associated with food away from home versus food at home in the United States. (1st July 2020) - Mackie, Chelsea; Wemhoff, Aaron P.
Abstract: Food consumption patterns continue to shift away from food at home (FAH) to food away from home (FAFH), and the prevalence of FAFH is significant in the developed world, so the comparative greenhouse gas emissions (GHGE) of FAH and FAFH are predicted in this study. The GHGE per mass of food acquisition in the U.S. is predicted to be 4.3 kg of carbon dioxide equivalent emissions (CO2 e)/kg food and 2.7 kg CO2 e/kg food for FAFH and FAH, respectively, which is attributed to higher chicken and beef consumption in FAFH. Predictions also suggest that 23% of total food acquisition by mass is by FAFH, with nearly half of the FAFH consumption in the form of beverages. FAFH was predicted to account for 33% of total food GHGE, which is nearly identical to the portion of daily energy intake by FAFH, and both FAFH and FAH meals are estimated to have a nearly constant value of 1.3 g CO2 e/kcal. FAFH meals are shown to be, on average, 330% higher in cost, 60% higher in GHGE, and 70% higher in energy content than FAH meals by mass. FAFH meals are also predicted to be higher in GHGE per mass than the 2, 000 calorie USDA recommended diet. The larger relative cost compared to relative GHGE suggests that the financial burden of shifting to FAFH mitigates the growth in GHGE attributed to the overall food system.